Efektivitas Penggunaan Oral Antidiabetes Kombinasi Glimepiride Dengan Pioglitazone Pada Pasien Dibetes Mellitus Tipe 2 - Mas Ulfa, Ninik; Arfiana, Nabila (Journal of Pharmacy and Science, 2020)
Diabetes mellitus is a disorder of chronic metabolic syndrome from carbohydrates, lipids and fats resulting from the deficiency of insulin in the body so that it can cause hyperglycemia. Oral Antidiabetic and Insulin is pharmacological therapy that can control blood sugar levels. This study aims to observe the effectiveness of Glimepiride combination therapy with Pioglitazone in type 2 DM patients with fasting blood Glucose and blood Glucose 2 hour post prandial parameters compared to pre and post values. This research method is observational with retrospective data collection and data analyzed descriptively. The sample size was 30 type 2 DM patients who received therapy after 6 months. The results showed that there were significant differences between the value of fasting blood Glucose pre and fasting blood Glucose post and blood Glucose 2 hour post prandial pre and blood Glucose 2 hour post from statistical analysis using paired t-test, with a value of Î± = 0.00 smaller than Î± = 0.05. This shows that the combination of Glimepiride with Pioglitazone is effective in blood glucose control in type 2 DM patients. Keywords: Dibetes Mellitus, Oral Antidiabetic, Glimepiride, Piogliatzone